Identifying historical and future global change drivers that place species recovery at risk - William L. Geary; Ayesha I. T. Tulloch; Euan G. Ritchie; Tim S. Doherty; Dale G. Nimmo; Marika A. Maxwell; Adrian F. Wayne (Global Change Biology, 2023)
Ecosystem management in the face of global change requires understanding how co‐occurring threats affect species and communities. Such an understanding allows for effective management strategies to be identified and implemented. An important component of this is differentiating between factors that are within (e.g. invasive predators) or outside (e.g. drought, large wildfires) of a local manager's control. In the global biodiversity hotspot of south‐western Australia, small‐ and medium‐sized mammal species are severely affected by anthropogenic threats and environmental disturbances, including invasive predators, fire, and declining rainfall. However, the relative importance of different drivers has not been quantified. We used data from a long‐term monitoring program to fit Bayesian state‐space models that estimated spatial and temporal changes in the relative abundance of four threatened mammal species: the woylie ( Bettongia penicillata ), chuditch ( Dasyurus geoffroii ), koomal ( Trichosurus vulpecula ) and quenda ( Isoodon fusciventor ). We then use Bayesian structural equation modelling to identify the direct and indirect drivers of population changes, and scenario analysis to forecast population responses to future environmental change. We found that habitat loss or conversion and reduced primary productivity (caused by rainfall declines) had greater effects on species' spatial and temporal population change than the range of fire and invasive predator (the red fox Vulpes vulpes ) management actions observed in the study area. Scenario analysis revealed that a greater extent of severe fire and further rainfall declines predicted under climate change, operating in concert are likely to further reduce the abundance of these species, but may be mitigated partially by invasive predator control. Considering both historical and future drivers of population change is necessary to identify the factors that risk species recovery. Given that both anthropogenic pressures and environmental disturbances can undermine conservation efforts, managers must consider how the relative benefit of conservation actions will be shaped by ongoing global change.